Pre-service Teachers’ Attitudes Toward Students With Behavioral Difficulties: Associations With Individual and Education Program Characteristics - Massé, Line; Nadeau, Marie-France; Gaudreau, Nancy; Nadeau, Sandy; Gauthier, Catherine; Lessard, Anne (Frontiers in Education, 2022)
Teachers’ beliefs towards students with special educational needs (SEN) in the regular classroom is a condition that may influence the implementation of inclusive education. Nevertheless, some studies suggest that teachers' attitudes or self-efficacy beliefs towards students with behavioral difficulties (BD) are quite negative, but much less emphasis has been placed on the factors and mechanisms contributing to these attitudes. The present study investigates associations between preservice teachers’ (PT) attitudes towards students with BD, PT’s individual characteristics including self-efficacy beliefs and PT’s education program characteristics. Participants surveyed were 1,499 PT enrolled in a four-years teacher education programs (bachelor’s degree) in the province of Quebec, Canada. Descriptive analysis showed that PT’s report generally positive attitudes towards students with BD on the three components of attitudes, while behavioral component were significantly more positive than the affective and cognitive components. Among the individual characteristics of PTs, the more advanced their academic level, the more negative their attitudes were on all three components. The characteristics related to the teacher education program (general vs special) and the number of hours of courses on the BD showed significant differences only on cognitive component. Results of the mediation analysis further indicated that the association between the PT’s characteristics and the three components of attitudes was mediated by PT’s self-efficacy beliefs. Results are discussed considering their implications for the field of teacher education.